Relasi Islam dan Hindu Perspektif Masyarakat Bali - I Gede Suwindia (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
This article explores the problem of relations between Mulsim and Hindu community in Bali. Methodologically, it consisted of three regions: Denpasar, Karangasem and Singaraja. Basically, the relation between Islam and Hindu in Bali has been strengthened by the Bali’s local culture which still continues to develop and exist until today. Genealogical relations due to marriage among families in the past and their generation’s nowadays also contribute significantly to the living harmony among Hindus and Muslims in Bali. Too, local governments trough Forum Kerukunan Antar Umat Beragama (Religion Followers Forum) and the Ministry of Religious Affairs facilitate wider medium of dialogues after the Reformasi era; therefore, relation among them remains constructive and puts forward local wisdom as the basis.